Quelques perspectives de développement de l’étude empirique des conflits internationaux - Braillard, Philippe (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
The empirical study of international conflicts has in the last two decades undergone a remarkable development. Careful examination of results so far obtained can however only produce feelings of dissatisfaction. The few correlations uncovered are usually so limited in scope that it is difficult to draw any conclusions whatsoever from them. This essay first of all suggests certain possible developments for empirical research, especially in areas which have been most neglected. The author goes on to show that the road on which such works are embarked, no matter how interesting, contains radical limits which can only invalidate the claims of practitioners of the empirical analysis of international conflicts to an elaboration of a truly explanatory theory. It will only be possible to discover explanatory elements if one undertakes a theoretical leap consisting in reorienting the study of international conflicts. The broad outlines of such a theoretical reorientation are described in the last part of the essay.